Damage control - Jance, Judith A. (New York : Harper, 2009)
Cochise County sheriff Joanna Brady investigates the death of handicapped woman who had wandered away from a care facility with a suspicious track record and the deaths of an elderly couple who were presumably consenting partners in a suicide pact.
Keywords: Brady, Joanna (Fictitious character) -- Fiction; Policewomen -- Fiction; Sheriffs -- Fiction; Cochise County (Ariz.) -- Fiction; Arizona -- Fiction; Mystery fiction